Expression, purification and crystallization of the putative transcriptional regulator MSMEG_6227 from Mycobacteria - Halas, Simon (Jihočeská univerzita, 2021)
MSMEG_6227, a putative transcriptional regulator from Mycobacterium smegmatis, was cloned and expressed in E. coli BL21 cells. The expressed protein was purified by chromatographic methods and an optimized protocol for the expression and purification of MSMEG_6227 was established. With the purified protein initial crystallization trials were set up, which need to be further optimized and scaled up in the future to resolve the X-ray structure of MSMEG_6227.
Expression, purification and crystallization of the putative transcriptional regulator MSMEG_6227 from Mycobacteria
Keywords: Mycobacteria; MSMEG_6227; Mycobacterium smegmatis; putative transcriptional regulator; Mycobacteria; MSMEG_6227; Mycobacterium smegmatis; putative transcriptional regulator